Gentoo G198 confocal right cornea - Peter Hadden; Akilesh Gokul; Satya Amirapu; Ratish Kurian; Charles McGhee; Jie Zhang (2022)
Right corneal confocal micrographs obtained post mortem from gentoo penguin G198